Spine-bellied sea snake (Hydrophis curtus) venom shows greater skeletal myotoxicity compared with cardiac myotoxicity. (1st March 2018) - Neale, Vanessa; Smout, Michael J.; Seymour, Jamie E.
Abstract: For the first time the impedance-based xCELLigence real-time cell analysis system was used to measure the myotoxicity of sea snake venom. With a focus on the spine-bellied sea snake ( Hydrophis curtus ), the venom of four sea snake species and three terrestrial snake species were compared for myotoxicity against a human skeletal muscle cell line (HSkMC). Hydrophis curtus venom was also tested on a human cardiac muscle cell line (HCM). Surprisingly, all four sea snake venoms tested on HSkMC produced an initial 100–280% rise in xCELLigence cell index that peaked within the first two hours before falling. The cell index rise of H. curtus venom was correlated with the WST-1 cell proliferation assay, which demonstrated an increase in mitochondrial metabolism. The myotoxicity of H. curtus was 4.7–8.2 fold less potent than the other sea snakes tested, the Australian beaked sea snake ( Hydrophis zweifeli ), the elegant sea snake ( Hydrophis elegans ) and the olive sea snake ( Aipysurus laevis ). If our cell-based results translate to H. curtus envenomations, this implies that H. curtus would be less myotoxic than the other three. Yet the myotoxicity of H. curtus venom to cardiac muscle cells was nine times weaker than for skeletal muscle cells, providing evidence that the venom has a selective effect on skeletal muscle cells. This evidence, combined with the slow-acting nature of the venom, supports a digestive role for sea snake myotoxins. Highlights: We tested Hydrophis curtus venom using an xCELLigence cell assay. The results imply that H. curtus venom has a selective effect on skeletal muscles. We show an increase in mitochondria activity and an xCELLigence readout rise. This may suggest ion influx into the mitochondria is occurring. Our research suggests a skeletal muscle digestive role for sea snake myotoxins.